Identifying and reporting position-specific countermovement jump outcome and phase characteristics within rugby league - McMahon, J. J.; Lake, J. P.; Comfort, P. (PLOS ONE, 2022)
The countermovement jump (CMJ) has been suggested to be an important test of neuromuscular performance for rugby league (RL) players. Identifying force platform-derived CMJ variables that may be more applicable to RL positions (e.g., forwards and backs) has yet to be fully explored in the scientific literature. The aim of this study was to identify RL position-specific CMJ force-time variables. Specifically, we aimed to compare select force-time variables from the countermovement (i.e., the combination of unweighting and braking) and propulsion phases of the CMJ between the global forwards and backs positional groups. We also aimed to compare typical (i.e., jump height) and alternative (i.e., take-off momentum) outcome CMJ variables between positional groups. Finally, we sought to visually present each individual player`s CMJ performance alongside the average data to facilitate the interpretation and reporting of the CMJ performances of RL athletes. Twenty-seven forwards and twenty-seven backs who competed in the senior men`s English RL Championship, performed three CMJs on a force platform at the beginning of the pre-season training period. There were no significant differences in any countermovement or propulsion phase variable between positions with just small effect sizes noted (P =0.09, d =0.46). Jump height (and so take-off velocity) was significantly greater for backs with moderate effects displayed (P = 0.03, d = 0.60). Take-off momentum (take-off velocity × body mass) was largely and significantly greater for forwards (P<0.01, d = 1.01). There was considerable overlap of individual player`s body mass and CMJ outcome variables across positions, despite significant differences in the mean values attained by each positional group. The results suggest that it may be beneficial for RL practitioners to identify player-specific, or at least position-specific, variables. As a minimum, it may be worthwhile selecting CMJ force-time variables based on what is considered important to individual player`s or small clusters of similar players` projected successes during RL competition.